Studies of Essential and Trace Elements in Some Fruits and Vegetables of Southwestern Bangladesh by PIXE Technique - Rahman, M.R.; Shariff, M.A.; Rahman, M.O.; Uddin, M.S.; Shafiq Ullah, A.K.M.; Shameem, M.A.; Hasan, M.M.; Hasan, S.J.; Huq, M.A. (Pakistan Journal of Nutrition, 2014)
Essential and trace elementals in some fruits and vegetables of southwestern Bangladesh have been measured using particle induced X-ray emission (PIXE) technique. The selected fruits and vegetables for study are usually consumed by all income groups of rural and city population. The samples were dried, pressed to make pellet and then bombarded with accelerated protons at 3.0 MV Tandem Accelerator facility of Bangladesh Atomic Energy Commission. The X-rays emitted in the irradiation were measured by HPGe-detector. The X-ray spectrum was analyzed using GUPIX software. A number of major and trace elements were found to be in varying concentrations in the investigated fruits and vegetables. The contents of K and Ca being notably large in some samples. No toxic elements were detected in the investigated samples.